ANALISIS PENGARUH TECHNO – FINANCE LITERACY DAN PRAKTEK ENTREPRENEUR RISK MANAGEMENT TERHADAP KINERJA USAHA KECIL MENENGAH (UKM) DI KABUPATEN LOMBOK TIMUR - Nadia Rizkiana; Siti Aisyah Hidayati; Embun Suryani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This study aims to determine the effect of financial literacy, technological literacy, and ERM practices on the performance of SMEs in East Lombok Regency. The type of research used in this research is associative research. The object of this research is SME actors who are engaged in the creative economy sector. The research population is 1,323 SMEs and the sample of this study is 50 respondents. The data collection method used is the survey sample method. The sampling technique used is purposive sampling. The data collection technique used in this study was interviews by distributing questionnaires to respondents. The type of data used in this study is qualitative data which is quantified using a Likert scale. The data source is in the form of primary data where the data is obtained directly from the owners of SMEs. The analytical tool used in this research is Multiple Linear Regression. Based on the results of the study, it was found that of the three variables that affect the performance of Small and Medium Enterprises in East Lombok Regency, only one variable has a positive and significant effect, namely the Financial Literacy variable (X1). Meanwhile, technological literacy (X2) and ERM practice (X3) have a positive but not significant effect on the performance of SMEs..